ANALISIS PERILAKU NASABAH TERHADAP MINAT BERINVESTASI DEPOSITO PADA BANK BRI - Meyken, Meyken; Agnes, Agnes; Ester, Ester; Asmida, Asmida; Roselina, Roselina; Siallagan, E. Hamonangan; Hasugian, Christnova (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the factors influencing Bank Rakyat Indonesia (BRI) customers’ interest in investing in deposits. The examined factors include attitudes, subjective norms, and perceived behavioral control based on the Theory of Planned Behavior (TPB). A quantitative approach was employed, with questionnaires as the data collection instrument. The sample consisted of 100 BRI deposit customers in Medan City, selected using purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings revealed that attitudes, subjective norms, and perceived behavioral control significantly influence deposit investment interest. These findings provide strategic recommendations for BRI to enhance the attractiveness of deposit products through customer education and supportive facilities